2021
DOI: 10.1158/1078-0432.ccr-20-3605
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-HER3 mAb Seribantumab Effectively Inhibits Growth of Patient-Derived and Isogenic Cell Line and Xenograft Models with Oncogenic NRG1 Fusions

Abstract: Purpose: Oncogenic fusions involving the neuregulin 1 (NRG1) gene are found in approximately 0.2% of cancers of diverse histologies. The resulting chimeric NRG1 proteins bind predominantly to HER3, leading to HER3-HER2 dimerization and activation of downstream growth and survival pathways. HER3 is, therefore, a rational target for therapy in NRG1 fusion-driven cancers.Experimental Design: We developed novel patient-derived and isogenic models of NRG1-rearranged cancers and examined the effect of the anti-HER3 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 34 publications
0
33
0
Order By: Relevance
“…xenograft models of various tumor types, including lung, ovarian and pancreatic tumors harboring different NRG1 fusions and, therefore, support clinical investigations of seribantumab in patients with these types of tumors [9].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…xenograft models of various tumor types, including lung, ovarian and pancreatic tumors harboring different NRG1 fusions and, therefore, support clinical investigations of seribantumab in patients with these types of tumors [9].…”
Section: Discussionmentioning
confidence: 57%
“…This expansion of knowledge has led to a rational adjustment in the seribantumab clinical development program, setting focus on solid tumors driven by NRG1 fusions [9,20]. Data from preclinical studies to date demonstrate encouraging antitumor activity of seribantumab in cancer cell lines and patient-derived…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). This observation was further validated by blocking HER3 with seribantumab, a humanized HER3-speci c antibody that demonstrated signi cant HER3 inhibition in previous studies 22,23,30 . We found that seribantumab completely blocked EC-induced HER3 and AKT phosphorylation in all cell lines we used (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Then we used CRC cell lines and demonstrated that liver ECs activated the HER3-AKT signaling pathway and increased CRC cells growth and resistance to 5-FU regardless of the KRAS mutation status. Moreover, the EC-induced pro-survival effects on CRC cells were completely blocked by HER3 siRNA knockdown, or with the HER3 antibody seribantumab that was used in preclinical and clinical studies [22][23][24] . Lastly, we used an orthotopic liver injection xenograft model and determined that blocking HER3 with seribantumab decreased CRC tumor growth and sensitized CRC to 5-FU chemotherapy.…”
Section: Introductionmentioning
confidence: 99%